Angular UI development with PrimeNG : build rich and compelling Angular web applications using PrimeNG - Jonna, Sudheer, 1987-; Varaksin, Oleg (Packt Publishing, 2017)
Unleash the power of PrimeNG components to design compelling user interface for your Angular applications About This Book Detailed insights into PrimeNG concepts, components and features with examples to help you make excellent User Interfaces for Angular web apps. Get familiar with themes, layouts and customization in real world applications. Develop Angular applications rapidly using advance tools and standards with best practices. Who This Book Is For This book is for everybody who would like to learn or create modern Angular based single page applications using PrimeNG component library. This book is a good choice for beginners to advanced users who are serious to learn modern Angular applications. The prerequisites for this book are some basic knowledge on the Angular 2+ version with TypeScript and CSS skills. What You Will Learn Setup PrimeNG projects with SystemJS, Webpack, and Angular CLI. Use theming concepts and layouts with grid systems and Bootstrap. Work with enhanced input, select, button and panel components. Apply countless DataTable features: sorting, filtering, grouping, and templating. Meet data iteration components: DataList, DataGrid, Tree, and so on. Build endless menu variations: SlideMenu, TieredMenu, MegaMenu, and so on. Visualize your data representations with PrimeNG charts and GMap components. Adopt best practices such as state management with @ngrx/store. Write unit and end-to-end tests with Jasmine, Karma, and Protractor. In Detail PrimeNG is a leading UI component library for Angular applications with 80+ rich UI components. PrimeNG was a huge success in the Angular world and very quickly. It is a rapidly evolving library that is aligned with the last Angular release. In comparison with competitors, PrimeNG was created with enterprise applications in mind. This book provides a head-start to help readers develop real-world, single-page applications using the popular development stack. This book consists of 10 chapters and starts with a short introduction to single-page applications. TypeScript and Angular fundamentals are important first steps for subsequent PrimeNG topics. Later we discuss how to set up and configure a PrimeNG application in different ways as a kick-start. Once the environment is ready then it is time to learn PrimeNG development, starting from theming concepts and responsive layouts. Readers will learn enhanced input, select, button components followed by the various panels, data iteration, over ...